2021
DOI: 10.1088/2053-1591/abd89d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and wear performance of Al/SiC surface composite prepared through friction stir processing

Abstract: In the present research work, AA7075 composite reinforced with silicon carbide particles has been fabricated using Friction stir processing (FSP). The silicon carbide particles having a size of 40 μm were placed in grooves of length 160 mm, width 2 mm, depth 3.5 mm, that were generated on the AA7075 plate. The square pin tool is utilized for fabricating the composite at two different rotational speed i.e. 700 and 1000 rpm. Effect of processing, particle addition and tool rotational speed is analyzed on mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The microstructure is finer when the volume fraction of the reinforcement particle is more (Pazhouhanfar and Eghbali, 2018). From Figure 5, it is evident that the wear rate decreases with increasing particulate content; this decrease might be attributed to an increase in these sample’s microhardness (Butola et al , 2021).…”
Section: Resultsmentioning
confidence: 97%
“…The microstructure is finer when the volume fraction of the reinforcement particle is more (Pazhouhanfar and Eghbali, 2018). From Figure 5, it is evident that the wear rate decreases with increasing particulate content; this decrease might be attributed to an increase in these sample’s microhardness (Butola et al , 2021).…”
Section: Resultsmentioning
confidence: 97%
“…In basic pH conditions, OH − anions plus H 2 O assaults the SiO 2 lavished glass matrix persuading the depolymerization cycle at the glass conformation. Hence, ceaseless disintegration can bring about dissolving the silicate matrix, with the consequent vanishing of the unique glass surface (Varshneya, 2013;Butola et al,2019Butola et al, , 2020Butola et al, , 2021. Previous in vitro studies suggested that surface erosion is a function of time, temperature, and pH (Xia et al, 2014;Bernhardt, 1941;Oyafuso et al, 2008;Gale and Darvell, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It was inferred from the previous statistical studies that applied load is comparatively a more influential tribological factor during nonlubricated sliding. [55][56] At applied minimal load of 15 N, outer layer of thermal treated FGMMC exhibits superior wear response (0.0001 mm 3 /Nm), when compared to the outer layer (0.000,119 mm 3 /Nm) of as-cast FGMMC. At 55 N, outer layer of thermal treated FGMMC exhibits lower wear response (0.00,024 mm 3 /Nm) compared to all other layers of both conditions (as-cast/thermal treated).…”
Section: Reciprocating Wear Testingmentioning
confidence: 99%